Reviews - Sandi Albertson-Shea; Susan A. Schiller; Jeffrey D. Wilhelm (Journal of the Assembly for Expanded Perspectives on Learning, 2001)
Sandi Alberston-Shea. Letters for the Living: Teaching Writing in a Violent Age. (Michael Blitz and C. Mark Huribert, 1999). Susan A. Schiller. Education and the Soul: Toward a Spiritual Curriculum. (John P. Miller, 2000). Jeffrey D. Wilhelm. Radical Presence: Teaching as Contemplative Practice. (Mary Rose O'Reilly, 1998). Back to the Archive
Keywords: Writing in a Violent Age; Spiritual Curriculum; Teaching as Contemplative Practice